Hypoxia-activated pro-drugs of the KDAC inhibitor vorinostat (SAHA) - Calder, EDD; Skwarska, A; Sneddon, D; Folkes, LK; Mistry, IN; Conway, SJ; Hammond, EM (Elsevier, 2020)
Hypoxia (lower than normal oxygen) is a characteristic of most solid tumours that results in poor cancer patient prognosis. The difference in cellular environment between normoxia (21% oxygen) or physoxia (4–7.5% oxygen) and hypoxia (<2.0% oxygen) causes increased resistance to radio- and chemotherapy, but also provides the opportunity to selectively release hypoxia-activated pro-drugs. This approach potentially allows targeting of chemotherapies, including lysine deacetylase (KDAC) inhibitors, to the hypoxic fraction of cells. Here, we report initial work on the development of KDAC inhibitors that are selectively released in hypoxic conditions. We have shown that the addition of a 4-nitrobenzyl (NB) or 1-methyl-2-nitroimidazole (NI) bioreductive group onto the hydroxamic acid moiety of SAHA, giving NB-SAHA and NI-SAHA, abolishes KDAC inhibition activity. Both NB-SAHA and NI-SAHA undergo enzyme-mediated bioreduction, in a hypoxia-dependent manner, to release SAHA selectively in <0.1% oxygen. This work provides an important foundation for further investigations into the targeted release of KDAC inhibitors in hypoxic tumours.